Het handelsmerk Zuid-Afrika: Enkele overpeinzingen rondom de toeristische berichtgeving - Zajas, Paweł (Department of Dutch and South African Studies, Faculty of English, 2009)
The article analyses the rhetoric of Polish photos and tourist advertisements concerning the South African Republic. It demonstrates the discrepancy between the strategies implemented by South African state organizations (International Marketing Council) and the picture of South Africa abroad – in Poland in this case. A claim is made that the Republic of South Africa advertised as tourist space has nothing to do with the visual identity of the country as it is promoted by the International Marketing Council which emphasizes the post-1994 democratic changes and the country’s interculturality.
Keywords: visual identity; tourist advertising; tourism